A SMOOTH DIFFUSION RATE MODEL OF WOOD DRYING:A SIMULATION TOWARD MORE EFFICIENT PROCESS IN INDUSTRY - Edi Cahyono; Yudi Soeharyadi; Mukhsar Mukhsar (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2008)
In this paper we consider modeling of wood drying process in an industry. The process is conducted in a kiln oven. Mathematically, the drying inside the wood is considered as an initial and boundary value problem. The model is a diffusion equation where the diffusion rate depends on the moisture content of the wood. We investigate a smooth diffusion rate and we compare the model with real data from an industry. The model shows a good agreement with the real data. Moreover, the model shows a smoother process of drying, which is more desirable by the timber and lumber industries to improve their current methods of drying.